(untitled) (Journal of Global Accounting, 2023)
To achieve better financial condition, an objective quality audit is needed which forms the basis for investors’ confidence on the integrity and reliability of financial reports. Financial reports are statements used to provide important information to the users so as to enable them assess the financial conditions and performance of related companies. This study examines the effect of audit quality on financial distress among insurance firms listed on the Nigerian Exchange Group. Specifically, the study examines the effect of audit fee, audit report lag and auditors’ independence on financial distress among insurance firms listed on the Nigerian Exchange Group. Financial distress was measured using the Altman Z-score ratios to determine the financial health status of twelve (12) Insurance companies listed on the Nigerian Exchange Group. The study adopts Ex-post Facto research design and the Linear Regression Analytical technique which was used to analyze data generated from 2013 – 2019 annual reports of insurance firms sampled. This was done with the aid of SPSS version 22. The study revealed that audit report lag has no significant effect on financial distress while audit independence and audit fee have positive and significant effect on financial distress. This study concludes that the financial condition of a firm is affected when there is lack of auditor independence. Based on the findings, the study recommends that the executives of Insurance companies should engage audit firms with an audit team that have more integrity and reputable character. Also, it is recommended that the firm should engage the services of auditors with the necessary technical and interpersonal skills to improve audit quality.